(untitled) (Teacher’s World: Journal of Education and Research, 2023)
The University of Dhaka was founded in 1921, marking the beginning of modern higher education in Bangladesh. The decision to build the University of Dhaka in Bangladesh was made as restitution for the 1905 partition of Bengal being declared invalid. The Special Issue honours the 100th anniversary of the University of Dhaka and the 50th anniversary of Bangladesh’s independence. As the pinnacle of academic quality, the university offers opportunities for researchers, professionals, and scholars to participate in theoretical debates, carry out empirical study, and contribute nationally and worldwide to share this pride. The Institute of Education and Research (IER) publishes a special edition of Teacher’s World on this occasion. This special issue examines the University of Dhaka’s contribution to Bangladeshi research and education. Five sub-themes are offered for the articles written by various academics and researchers. Father of the Nation’s Philosophy, Educational Development in Independent Bangladesh, Dhaka University’s Role in Education Reform, Educational Research and Dhaka University, and Trends and Emerging Issues in Education are among the sub-themes. Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.1-6